Forming of Word: Morphological Analysis in â€œBittersweet in Your Mouth, Can Your Stomach Doubt?â€ Fiction Story by @vvrites (On Twitter) - Simanjuntak, Mutiara Nuraini; Marbun, Fitriani; Lubis, Ridzky Hidayah; Damanik, Emiliya Sukma Dara (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
New words are needed not only to increase our vocabulary but also to create new sentences. The new words purchased by the word training process can be made in many ways. One of the most commonly used methods to form new words is assigned by prefix or suffix. The aims of this study is to analyze the morphological word formation in @vvrites (on twitter) Fictional Story â€œBittersweet on Your Mouth, Can Your Stomach Doubt?â€. The method used by the researcher is a qualitative method, where the researcher investigate the formation of words in the fictional strory from @vvrites ( on twitter ) entitled â€œBittersweet on Your Mouth, Can Your Stomach Doubt?â€ on twitter. The result of this study are the researchers found some types of forming words that will be explained one by one.Keywords : Word Formation, Fiction, Twitter